Management of Cleft Lip and Palate in Pediatric Dentistry: A Review - Subhangi Chandan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Birth of a child is considered the happiest moment of a parent’s life and magical experience where Godentitles a mothering power of creation. When a child born with a cleft, it represents a disaster for parents.Surgical restoration of soft tissue continuity of the lip and palate consequences in an approximation of themaxillary segments irrespective of surgical technique. The degree of maxillary width reduction depends onseveral factors, including surgical technique, the surgeon’s skill, scar formation, degree of tissue deficiency,and timing procedures.